MULTIPLE ENDOCRINE NEOPLASIA IN A NEWBORN - Pereda, José (2015)
The case of a newborn with multiple endocrine neoplasia is presented. Emphasis is placed on the differences between classical types and the one presented here. The nature of the proliferative lesions is also commented.